Dual‐port network‐based impedance modelling and AC‐port characteristic analysis of wound rotor synchronous machine for more electric aircraft - Zixiao Xu; Yang Qi; Weilin Li; Yu Wu; Josep M. Guerrero; Juan C. Vasquez (IET Electric Power Applications)
Abstract Due to the increasing variety of converters in more electric aircraft (MEA), the stability of the MEA power system has become a critical issue that receives wide concerns. As the primary power source for MEA, the wound rotor synchronous machine (WRSM) greatly affects the stability of the whole power system, and therefore accurate modelling of the WRSM serves as the basis for the analysis of system characteristics and even stability. Nevertheless, the complex structure and coupling of WRSM bring great challenges to small‐signal modelling methods. This paper introduces a novel method to model the WRSM in a modular and cascaded manner. Instead of deriving the complex transfer function, the proposed method uses a dual port to model each component. By connecting the dual port of each component from the rear stage to the front stage in a cascaded way, a dual‐port network can be built to describe the external impedance characteristics of the WRSM. Kirchhoff law can be applied to calculate the impedance by circumventing the complicated decoupling process. The proposed dual‐port network model has been validated on a hardware‐in‐loop platform. Furthermore, the output impedance characteristics of the AC port has also been analysed with the proposed model.